2007
DOI: 10.1016/j.jaci.2006.12.649
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes from familial cold autoinflammatory syndrome patients are activated by mild hypothermia

Abstract: These results confirm the central role of IL-1beta in FCAS and support the use of IL-1 targeted therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 29 publications
(35 reference statements)
2
48
0
Order By: Relevance
“…The cold-induced inflammation seen in patients with FCAS was simulated ex vivo. Patient cells spontaneously released IL-1β in response to incubation at 32°C, a result that was blocked by anakinra, and that confirmed that modest cold exposure can trigger IL-1β release in these patients [21]. The role of mutant CIAS1-induced necrosis described in an in-vitro model needs further evaluation [22].…”
Section: Advances In Our Understanding Of the Pathophysiology Of Monomentioning
confidence: 81%
“…The cold-induced inflammation seen in patients with FCAS was simulated ex vivo. Patient cells spontaneously released IL-1β in response to incubation at 32°C, a result that was blocked by anakinra, and that confirmed that modest cold exposure can trigger IL-1β release in these patients [21]. The role of mutant CIAS1-induced necrosis described in an in-vitro model needs further evaluation [22].…”
Section: Advances In Our Understanding Of the Pathophysiology Of Monomentioning
confidence: 81%
“…Peripheral blood monocytes from patients with FCAS spontaneously secrete IL-1β when incubated at 32°C (14), as do murine cells harboring the L351P mutation (9). ELISAs for IL-18 demonstrated that FCAS CreT BMDCs, but not WT or MWS CreT BMDCs, also secrete IL-18 spontaneously when incubated at 32°C ( Figure 1B).…”
Section: Nlrp3 Mutant Mouse and Caps Patient Hematopoietic Cells Demomentioning
confidence: 96%
“…The infl ammasome is a multiprotein complex composed of a sensor NLR protein, the PYD-and CARD-domain containing adapter protein ASC, and the inflammatory protease caspase-1 (Martinon et al, 2002). Once activated, NLR changes conformation to recruit ASC and assemble the infl ammasome secrete IL-1β and IL-18, and IL-1 receptor antagonists have been proved to be an effective treatment for these autoinfl ammatory syndromes (Hoffman et al, 2004;Rosengren et al, 2007). Recently, increasing evidence indicates that dysregulated production of IL-1β are implicated in the pathophysiology of several common diseases, including atherosclerosis (Duewell et al, 2010), osteoarthritis (Denoble et al, 2011), metabolic syndrome (Strowig et al, 2012), and type 2 diabetes (Zhou et al, 2010).…”
Section: Introduction Of Inflammsomesmentioning
confidence: 99%